An intelligent gel designed to control the spontaneous combustion of coal: Fire prevention and extinguishing properties. (15th December 2017) - Cheng, Weimin; Hu, Xiangming; Xie, Jun; Zhao, Yanyun
Graphical abstract: Highlights: A novel mining fire extinguishing material is proposed. A self-foaming gel mixed with expandable graphite to form an intelligent gel (IG). IG can steadily lower the temperature of the fire source, reducing the amount of CO. FT-IR indicated inhibition of the oxidation of hydroxyl with IG. Abstract: A new type of mining fire-extinguishing material designed to prevent the spontaneous combustion of coal is presented. Through the graft copolymerization of corn straw, 2-acrylamide-2-methylpropanesulfonic acid (AMPS), and acrylic acid (AA), a corn straw-co-AMPS-co-AA hydrogel was synthesized. A chemical foaming agent was then added to the hydrogel, resulting in a self-foaming gel, which was subsequently mixed with expandable graphite to create an intelligent gel. Compared to temperature-sensitive and polyacrylamide gels, this intelligent gel exhibited good thermal stability, as well as adhesion and swelling at high temperatures. Fire-extinguishing experiments revealed that the intelligent gel could cover the surface of burning coal, thereby significantly reducing the ignition source temperature, thermal radiation, and amount of CO generated. Infrared spectrum analysis showed that the IG sample with 10% expanded graphite could inhibit the oxidation of the hydroxyl group during the heating process. The fire-extinguishing performance of the intelligent gel was found to be superior to those of the other gels, as it prevented re-ignition. Thus, this gel is an ideal fire prevention and control material, especially for controlling the spontaneous combustion of coal.